Research progress in effects of biochar on transport of inorganic pollutants in soil - ZHANG Dong; LIU Xingyuan; ZHAO Hongting (浙江大学学报. 农业与生命科学版)
Biochar is a carbon-rich product obtained from thermal treatment and pyrolysis of various plant-and animal-based biomass. The biomass for preparation of biochar had extensive sources, and the treatment is usually easy-operation, mainly thermochemical decomposition under a poor-oxygen condition. Biochar has been considered as a low-cost and high-efficiency sorbent for both organic and inorganic contaminants including heavy metals, radioactive elements, nitrogen and phosphate, due to its abundant O-containing functional groups and surface charges, advanced micro-and macro-pore structures, and rich carbon content.In this paper, recent research progress on biochar with regards to its mechanisms and potential applications in remediation of inorganic contaminated soils was reviewed. The key parameters controlling biochar’s properties include pyrolysis temperatures and feedstock types, resulting in biochar with great difference in surface areas, pore size distribution, pH, H/C ratio, ion-exchange capacity, and carbon content. Therefore, the sorption mechanisms of inorganic pollutants varied with different properties of biochar. The sorption mechanisms of inorganic pollutants such as heavy metal, radioactive elements, nitrogen and phosphate were summarized as well as their potential applications in real soil condition. Several different possible mechanisms were proposed: 1) electrostatic outersphere complexation due to surface cationic exchange;2) surface complexation with active O-containing functional groups such as carboxyl and hydroxyl groups;3) electrostatic attraction of anionic inorganic pollutants such as phosphate and arsenic to protonated groups under alkaline pH;4) co-precipitation of heavy metal and phosphate with organic matter and mineral oxides on surface of the biochar or pre-sorbed metal ions;5) specific binding of iodide with aromatic carbon in biochar;6) to donate electrons for mitigating/reducing heavy metal such as chromium;7) physical adsorption of heavy metals onto biochar’s surface;8) changing the pH of point of zero charge (pHpzc) to immobilize or mobilize heavy metals.Generally and undoubtedly, the use of biochar as an environmental sorbent can have strong implications. It can effectively sorb various organic and inorganic contaminants in aqueous solutions. However, due to soil complexity, whether biochar is suitable for the remediation of inorganic contaminated soil is still unclear. These confused results could attribute to: 1) high dissolved organic carbon contents of soil at the increased pH induced by biochar addition may mobilize heavy metal leaching and/or form high available species;2) electrostatic repulsion between anionic heavy metal ions and negatively charged biochar surface may enhance the desorption of heavy metal from soil-biochar matrix;3) changing soil pH may result in mobilization or immobilization of heavy metals;4) the transportation of biochar in soil system may influence the mitigation of sorbed heavy metals;5) the availability of heavy metal sorbed by biochar to soil microorganism or plants;6) the stability and biodegradation of biochar is also an uncertain factor for the application of biochar in the remediation of inorganic contaminated soil.Based on the limited information, we proposed that biochars, especially those pyrolyzed at high temperature were suitable for the remediation of the low-pH and/or low dissolved organic carbon soil contaminated with cadmium, lead, copper, zinc and other heavy metals. Furthermore, further researches on interactions among soilbiochar-pollutants and field applications for remediation of contaminated soil are urgently needed.